RESEARCH ON COMPETENCY MODEL OF HEALTH EMERGENCY MANAGEMENT CADRES BASED ON SCL-90 PSYCHOLOGICAL EVALUATION - Li, Weichun (The international journal of neuropsychopharmacology, 2022)
Abstract Background Since entering the 21st century, a series of public health emergencies such as SARS, influenza A and covid-19 in 2019 have occurred continuously, causing serious damage and loss to people's lives and property. In the process of social transformation and economic globalization, the probability of various new public health events is increasing, the number of group unexplained diseases is increasing, and the cross-border and cross-border impact of the virus is rising, which has brought a lot of new challenges to China's health emergency management. Health emergency management cadres are the key groups to deal with public health emergencies. So far, the existing theoretical research results have not established a unified evaluation standard and detailed evaluation index for the post competence of health emergency management cadres, which will not be conducive to the comparison and application of evaluation results. Based on the psychological test results, this study constructs the competency model of health emergency management cadres and compiles the evaluation scale, so as to provide an objective evaluation tool for comprehensively measuring the post competency of health emergency management cadres. Subjects and Methods Competency elements, also known as competency, refer to the potential characteristics that can distinguish outstanding people from ordinary people in work (or organization and Culture). Grounded theory research is a qualitative method, which refines the concept of the research object and the relationship between its elements by encoding the collected data sentence by sentence. The grounded theory (GT) was used to conduct psychological evaluation and behavioral interviews with health emergency management experts to construct the competency element system of health emergency management cadres. Through exploratory factor analysis, the competency model of health emergency management cadres was constructed. The competency evaluation of health emergency management cadres should not only be based on scientific competency elements, but also establish specific quantitative items to test the competency level of this group. According to the competency model of health emergency management cadres, the corresponding Likert five point evaluation scale is compiled in order to provide a management tool for the evaluation of the competency of health emergency management cadres. At the same time, SCL-90 scale was used to measure the psychological state of these cadres. Results The competency model of health emergency management cadres was composed of three competency dimensions: specialization, professional quality and professional ability, and 16 competency dimensions. On this basis, the competency evaluation scale of health emergency management cadres was compiled. The final scale contains 43 items. Conclusion The scale has good reliability, validity and fit. It is a reliable, effective and applicable scale. It can not only be used as a tool to evaluate the post competence of health emergency management cadres, but also provide a scientific basis for the selection, training and self-assessment of health emergency management cadres. In short, we should carry out relevant combination of industry and education according to our own advantages and characteristics. Make clear the goal of motivation by example, and regularly hold activities such as successful model sharing, experience introduction and project display, so as to set a successful example for positive emotions, clarify the specific objectives of the activities, form a strong psychological momentum, stimulate internal potential and help the realization of positive behavior. We should strengthen professional guidance, give full play to the concentration of professionals, high intelligence, professional knowledge in business fields, and give full play to the advantages of talents and intelligence. We can organize experts and scholars to establish a professional bid winning guidance team, give full play to the business projects of experts and scholars in their respective fields, and carry out scientific research on relevant projects. Acknowledgements Fund Project: 1. CAAC safety capability project: research on theoretical system of civil aviation supervision with Chinese characteristics; 2.CAAC educational talent project:(Project No.:MHJY2022018) construction of competency model and assessment scale development for senior civil aviation inspectors; 3.Special fund project of Central Universities basic scientific research business (Project No.: J2021-114): Competency model construction and evaluation scale development of civil aviation health emergency management cadres.